Statin-induced necrotizing autoimmune myopathy: an extremely rare adverse effect from statin use. Issue 6 (2nd November 2019) - Sharma, Priyadarshani; Timilsina, Bidhya; Adhikari, Janak; Parajuli, Prem; Dhital, Rashmi; Tachamo, Niranjan
ABSTRACT: Statins are widely prescribed medications to prevent cardiovascular events. While self-limited statin myopathy is relatively common, statin-induced necrotizing autoimmune myopathy (SINAM) is extremely uncommon, with incidence of two cases per million per year. We present a case of SINAM after a decade of atorvastatin use, leading to debilitating weakness. A 71-year-old male presented with recurrent falls due to extreme bilateral lower-extremity weakness without pain or sensory changes. No fever, chills, rash, joint pain, recent infection or medication changes were reported. Reported taking atorvastatin 80 mg daily for 10 years. Physical examination revealed significant muscle wasting on right deltoid and proximal muscle weakness in all extremities. Lab tests included elevated creatinine kinase, aldolase, ESR, CRP and transaminases. Anti-HMGCR antibody was significantly elevated. TSH, serum protein electrophoresis and RPR were unremarkable. ANA, Anti-Jo-1, anti-Mi2, anti-SRP, anti-ds-DNA, anti-SSA and anti-SSB antibodies were negative. MRI of thigh revealed diffuse myositis. Electromyogram revealed an acute myopathic process. Muscle biopsy showed muscle necrosis and C5b-9 sarcolemmal deposits on non-necrotic fibers without rimmed vacuoles. He was diagnosed with SINAM. Statin was discontinued, and steroid, immunoglobulins and azathioprine were started with gradual improvement. Unlike the self-limiting statin myopathy, SINAM is more severe and is associated with significant proximal muscle weakness, markedly elevated CK and persistent symptoms despite statin discontinuation. Anti-HMGCR antibodies are present in 100% of cases. Immunosuppressants are the mainstay of treatment, and statin rechallenge should never be done in these cases. Although relatively rare, physicians should be cognizant of SINAM.